Right ventricular dysplasia: a clinical and pathological study of two families with left ventricular involvement. Issue 2 (February 1993) - Miani, D; Pinamonti, B; Bussani, R; Silvestri, F; Sinagra, G; Camerini, F
Abstract : BACKGROUND--Right ventricular dysplasia is a heart muscle disease of unknown cause that is often familial and is anatomically characterised by adipose or fibroadipose infiltration of the right ventricular myocardium. It is generally regarded as a selective disorder of the right ventricle. AIM--To investigate the prevalence and characteristics of left ventricular involvement in two families in which at least one member had right ventricular dysplasia confirmed at necropsy. METHODS AND RESULTS--Eight patients were found to be affected by right ventricular dysplasia. In three of them this was confirmed at necropsy. Echocardiography or angiography or both showed left ventricular involvement in seven. This ranged from localised wall motion abnormalities to moderate or severe left ventricular dysfunction. The disease was progressive in four cases. At necropsy the left ventricular myocardium showed predominant fibrosis and degenerative changes of the myocardial cells. There were areas of myocardial thinning with fatty infiltration at the apex in two patients. CONCLUSIONS--Familial right ventricular dysplasia can be a progressive disorder that affects the left ventricle. Advanced disease may be clinically confused with dilated cardiomyopathy.